The Role of Educational Support in Overcoming Time Management Challenges for UK Career-Transitioning Adult Learners - E. G. Whitfield; Thomas Gallagher (Journal of Advanced Research in Education, 2024)
Career-transitioning adult learners in the UK face significant time management challenges as they balance professional, academic, and personal responsibilities. Educational support systems, including flexible learning options and technological tools, play a crucial role in addressing these challenges. This paper explores the impact of such support on learners’ ability to manage their time effectively, improve academic performance, and reduce stress. By examining case studies and current educational practices, the paper highlights successful strategies and offers recommendations for enhancing support systems. Future innovations and policy changes are also discussed to provide a comprehensive framework for supporting adult learners in their career transitions.